Analysis of Differences in Volatile Components of Rucheng Baimao (Camellia pubescens) Black Tea in Different Seasons - Junye Zhu; Yuebin Zhou; Haitao Wen (Foods)
At present, there are few studies on seasonal differences in the aroma quality and volatile components of Rucheng Baimao (Camellia pubescens) black tea. In this study, sensory evaluation and volatile component analysis were carried out on one sample of Rucheng Baimao black tea corresponding to spring, summer, and autumn, respectively. The results of sensory evaluation showed that the black teas of all three seasons had floral aromas. However, the aroma quality of spring black tea was the best, followed by that of autumn black tea, and summer black tea was the worst. The analysis of volatile components showed that alcohols, esters, and alkanes were the main substance categories. In addition, the results of the aroma index were consistent with those of the sensory evaluation, indicating that spring black tea had the best aroma quality, followed by autumn black tea and then summer black tea. Eleven key differential volatile components were screened by combining PLS-DA analysis (VIP > 1, p < 0.05) and rOAV > 1. Among them, geraniol, methyl salicylate, nonanal, and (E)-citral accumulated the most in spring black tea, linalool, phenylacetaldehyde, benzaldehyde, phenethyl alcohol, benzyl alcohol, and β-ionone accumulated the most in summer black tea, and trans-nerolidol accumulated the most in autumn black tea. This study aims to provide a theoretical reference for the regulation of the aroma quality of Rucheng Baimao black tea.